Punitive privatization in Mexico: Labor subjectification in relation to prison outsourcing - Hoyos-González, Pablo (2023)
Given the scarcity of research on the impact of the privatization of the prison system in Latin America, we take the Mexican case with the aim of problematizing the implementation of prison outsourcing and the accreditation of new prisons by the American Correctional Association (ACA). In historical context, we will see how the privatization of prisons and the expansion of precariousness and incarceration as a form of government began with the signing of the Merida Plan, amidst the crossfire of the war declared against drug trafficking, which brought the neoliberalizing impulse with which the prison outsourcing model would begin. Based on the methodology of situated narratives, we problematized, together with a prison worker, the subjectivizing conditions that would mobilize prison outsourcing among new employees in this type of prisons. We also analyzed the details of the labor activity regime that the ACA standards require of them. We conclude that prison outsourcing poses a labor horizon of precariousness in which those who integrate it are required to progressively develop a multipurpose technical toolbox; this kind of polytechnical worker must also be subject to the activity regime of the ACA and to the punitive sensitivity of the actuarial model.